An analysis of tax compliance problems of small to medium enterprises in a Zimbabwe economic environment - Tavarwisa, Enfa (Midlands State University, 2020)
Tax is one of the major stream of revenue to the government of Zimbabwe and thus the Zimbabwe Revenue Authority must continuously assess and improve its operations to maximise revenue collections and efficiency in administering tax collection. The Revenue Authority was continually missing its revenue collection targets for period 2012 up to 2016 even though it was the same period SMEs were emerging and making enormous economic contributions to the national GDP and country’s budget. This therefore suggested that SMEs were not complying with their tax obligations thus research objectives were to investigate the relationship between attitudes, normative beliefs and control beliefs with tax compliance to establish the problems being encountered by SMEs in tax compliance. A detailed literature review was outlined and variables as attitude, subjective norms and perceived behavioural control towards tax compliance were detailed. The research was a quantitative survey carried at Kurima house with different client care offices being the stratums from which random respondents were selected to answer the questionnaires. Most of the respondents agreed that planned behavioural control influences tax compliance but from the analysis done using Pearson’s correlation it came out that there is a negative relationship between attitudes and tax compliance as well as perceived behavioural control but there is a positive relationship between tax compliance and subjective norms. In addition, impact of planned behavioural control on tax compliance, linear regression was employed and both attitudes and perceived behavioural control have no significant impact on tax compliance whilst subjective norms had a positive relationship. Therefore, the Zimbabwe Revenue Authority may use the results obtained from this research to identify areas of concern that influence tax compliance if added in the tax environment and if not added will create a problem. Future studies can dwell on the same research but however increase sample size in order to increase the certainty from which inferences would be drawn